TARI TOTOKNG DALAM UPACARA ADAT NAIK DANGO SUKU DAYAK KANAYATN DI DESA BABANE KABUPATEN BENGKAYANG (TINJAUAN SOSIOLOGI) - Diana, Wahyu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study explores the Totok'ng dance within the Naik Dango ceremony of the Dayak Kanayatn tribe in Babane Village, Indonesia. It examines the dance's role in the ceremony through written descriptions, pictures, and videos. The research focuses on the background and rituals of the Naik Dango ceremony, with a particular emphasis on the sociological significance of the Totok'ng dance. It uses a descriptive qualitative approach with sociological methods. Data collection involves observation, interviews, and document analysis. To ensure data accuracy, the research employs triangulation and verification techniques. By analyzing the ceremony, the study aims to reveal the connection between the Dayak Kanayatn community's beliefs and their cultural practices. It highlights the concept of Jubata, their ancestral spirits, and their belief in supernatural forces influencing daily life and agricultural success. The Naik Dango ceremony itself consists of two main rituals: the Nyangahatn ritual and the Totok'ng dance, followed by a rice offering ritual. Finally, the study emphasizes the importance of community cooperation in preparing and performing the Totok'ng dance within the Naik Dango tradition.